Does Birthplace Diversity Affect Economic Complexity? Cross-Country Evidence - Dany Bahar; Hillel Rapoport; Riccardo Turati (Institute of Labor Economics (IZA), 2020)
We empirically investigate the relationship between a country's economic complexity and the diversity in the birthplaces of its immigrants. Our cross-country analysis suggests that countries with higher birthplace diversity by one standard deviation are more economically complex by 0.1 to 0.18 standard deviations above the mean. This holds particularly for diversity among highly educated migrants and for countries at intermediate levels of economic complexity. We address endogeneity concerns by instrumenting diversity through predicted stocks from a pseudo-gravity model as well as from a standard shift-share approach. Finally, we provide evidence suggesting that birthplace diversity boosts economic complexity by increasing the diversification of the host country's export basket.
Keywords: F22; O31; O33; 330; economic complexity; birthplace diversity; immigration; growth